Au24(SAdm)16 Nanomolecules: X‑ray Crystal Structure, Theoretical Analysis, Adaptability of Adamantane Ligands to Form Au23(SAdm)16 and Au25(SAdm)16, and Its Relation to Au25(SR)18 - Crasto, David; Barcaro, Giovanni; Stener, Mauro; Sementa, Luca; Fortunelli, Alessandro; Dass, Amala (Journal of the American Chemical Society, 2014)
Here we present the crystal structure, experimental and theoretical characterization of a Au24(SAdm)16 nanomolecule. The composition was verified by X-ray crystallography and mass spectrometry, and its optical and electronic properties were investigated via experiments and first-principles calculations. Most importantly, the focus of this work is to demonstrate how the use of bulky thiolate ligands, such as adamantanethiol, versus the commonly studied phenylethanethiolate ligands leads to a great structural flexibility, where the metal core changes its shape from five-fold to crystalline-like motifs and can adapt to the formation of Au24±1(SAdm)16, namely, Au23(SAdm)16, Au24(SAdm)16, and Au25(SAdm)16. The basis for the construction of a thermodynamic phase diagram of Au nanomolecules in terms of ligands and solvent features is also outlined.